Control interno a la cooperativa de ahorro y crédito Santa María Manga del Cura Ltda.; cantón el Carmen, provincia Manabí, año 2013 - Guerrero Anchundia, Vanesa Del Rocío (2013)
The proposal raised was held in Santa Maria Complex sector Manga del Cura is a not yet defined area is located at Av. Manabi and June 26th street side of the agro veterinary Rancho. Aimed to assess the internal control over Cooperative Savings and Credit St. Mary of the priest Manga Ltd., and its impact on decision-making by 2013. The specific objectives were to conduct an assessment of compliance with the regulations of the Savings and Credit Cooperative Santa Maria del Cura Manga Ltd., 2013. Apply indicators to measure the effectiveness and efficiency in the economy. Issuing the internal control report to the Cooperative . Create an Internal Control Manual. The results show that processes in the Savings and Credit Cooperative Santa Maria del Cura Manga Ltd., established drawbacks that sometimes occurs in the process . According to the situation assessment of the Savings and Credit Cooperative Santa Maria del Cura Manga Ltd. in the period 2013 through the SWOT system, it was identified that the company has not documented its mission, vision , nor is intended Internal Rules with business policies to benefit the entire organization. The evaluation of internal control of the Savings and Credit Cooperative Santa Maria del Cura Manga Ltd., presented a moderate control. The findings in the evaluation of internal control of the Cooperative Credit Union Santa María del Cura Manga Ltda, a report by determining the effect has caused delays in the process and is affected by the performance of the entity. Furthermore, the company does not have a manual function that defines the responsibilities of staff, also has documented policies and internal control procedures , thereby affecting the outcome of the Savings and Credit Cooperative Santa Maria del Cura Manga Ltd.